If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-4) + -2y = 0 Multiply 4 * -4 -16 + -2y = 0 Solving -16 + -2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -2y = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -2y = 0 + 16 -2y = 0 + 16 Combine like terms: 0 + 16 = 16 -2y = 16 Divide each side by '-2'. y = -8 Simplifying y = -8
| 2(x+1)+3(2x-5)=35 | | (5x^4)-2x-4.25=0 | | 4(x+60)+4x=1000 | | 25-7x+3=-3x-11+15x | | 3(-9)+5(-3)+6= | | 7(4)-3(-2x)= | | x^2-9/(x^2)-4 | | 2*0.6*5*5*5= | | 2(0.6)(125)= | | 1/2(4)(-4) | | (5y^2-5y-2)(y^2-5y+5)= | | 16+12-2= | | (12-2)(4+6)= | | -2-9x=-12x+1 | | (4/r^2)+(3/r)=1 | | (9+4-2)*(5-6)= | | 2x-y=3x^2n | | 3x^2-1x-10= | | 4nx=13-2n | | 8x^2-8x-48= | | 9x^2-3x+18= | | (-11+x)(3x-7)= | | 5*-2*-9= | | (4+6)-2= | | (4-2)(9*6)+4= | | an=2(1) | | 4000/x=0 | | y^2+3y+10=0 | | (3b+4b^2-2b^4)+(5b+8b^2+2b^4)-(5b^4+5b^2)= | | 4x^4+8x^3-7x^2+4x-28=0 | | 4x+3x=432 | | 6x^2+66x+168x=0 |